If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3(4h-1)=2(3-h)
We move all terms to the left:
3(4h-1)-(2(3-h))=0
We add all the numbers together, and all the variables
3(4h-1)-(2(-1h+3))=0
We multiply parentheses
12h-(2(-1h+3))-3=0
We calculate terms in parentheses: -(2(-1h+3)), so:We get rid of parentheses
2(-1h+3)
We multiply parentheses
-2h+6
Back to the equation:
-(-2h+6)
12h+2h-6-3=0
We add all the numbers together, and all the variables
14h-9=0
We move all terms containing h to the left, all other terms to the right
14h=9
h=9/14
h=9/14
| 7x+x-54=8x | | 17.50x+150+220=1157.50 | | 3n^2-3n-1728=0 | | 4.5+6x=12. | | 18m−17m=14 | | 3(11x+1)=12(4x-6) | | 0.5x+8-10=6 | | x+8/3-5=4 | | (3x+5)=(x-25 | | -3(1+8n)=28+2n | | 23-(3c+4)=2(c+5)+c | | (6x-7)=(5x+16) | | 10=6+t8 | | 7=9y–20 | | 3+x+8/3+1=0 | | -2(-c-12)=-2c-12= | | -12+5k=15-7 | | 42x+4=9x-8x | | f=21/ | | 5(-3x-2)+(x-3)=-4(4x+5)+13 | | 29x+3=20x-10x | | 123x+5=8x-x | | -7(-5+2r)=91 | | x/(1-x)=0.66 | | 12.4w=8.4w+8 | | 13+5x=4(−x+3)−35 | | 15.6k=8.6k+56 | | 20.1r=11.1r+81 | | 2(4y+1)=8y+2 | | 13.4y=10.4y+9 | | 4x+56=18 | | -1(-3+5v)=-22 |